2019
DOI: 10.31557/apjcp.2019.20.2.595
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between the Dosimetric and Clinical Outcomes of Tomotherapy and 3D Conformal Radiotherapy in Gastric Cancer Treatment

Abstract: Introduction:Previous studies comparing tomotherapy (TOMO) and three dimensional (3D) conformal radiotherapy (3DCRT) in gastric radiotherapy are limited and tend to be based on dosimetry. The aim of the present study was to evaluate the clinical outcomes of these two treatment modalities. Methods:A total of 51 patients diagnosed with gastric cancer who were treated with postoperative adjuvant chemoradiotherapy and had subtotal/total gastrectomy and D2 lymphatic dissection were recruited to the present study: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…There were 46 records were retrieved for full-text evaluation, while 32 studies were excluded because 10 records were not about GC, 7 studies not used PT, HIB therapy, or TOMO as radiotherapy measures, 9 studies were about GC radiotherapy dosimetry research, 2 studies [16, 17] were about GC cell irradiation research, and 2 were repeated. Eventually, there were 14 studies [18-31] met the eligible criteria were included for qualitative analysis, of which ten studies [18-20, 22-26, 28, 29] researched GC radiotherapy, 4 studies [21, 27, 30, 31] were about LMGC radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 46 records were retrieved for full-text evaluation, while 32 studies were excluded because 10 records were not about GC, 7 studies not used PT, HIB therapy, or TOMO as radiotherapy measures, 9 studies were about GC radiotherapy dosimetry research, 2 studies [16, 17] were about GC cell irradiation research, and 2 were repeated. Eventually, there were 14 studies [18-31] met the eligible criteria were included for qualitative analysis, of which ten studies [18-20, 22-26, 28, 29] researched GC radiotherapy, 4 studies [21, 27, 30, 31] were about LMGC radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…And all studies with a language of English. Study sites were indicated in 7 [18, 20, 21, 25, 27, 29, 31] studies and research periods were described in 8 studies [20, 21, 25, 27, 29-31]. As to intervention measures, 85.7% (12/14) of included studies were single arm without comparison tests.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations